Alleviation of TGF‐β1 induced tubular epithelial–mesenchymal transition via the δ‐opioid receptor. (11th July 2020) - Luo, Fengbao; Xu, Renfang; Song, Guanglai; Xue, Dong; He, Xiaozhou; Xia, Ying
Abstract : Renal fibrosis is a common pathological feature of progressive chronic kidney disease (CKD). It is indicated that transforming growth factor‐β1 (TGF‐β1) plays as a central mediator in renal fibrosis. The present study aimed to investigate the role of δ‐opioid receptor (DOR) on renal fibrosis of the rat renal proximal tubular epithelial cell line (NRK‐52E) induced by TGF‐β1 and to elucidate its underlying mechanism, as well as its involvement in signaling pathways. Cells were treated with TGF‐β1 (10 ng·mL −1 ), along with a specific DOR agonist (UFP‐512) or naltrindole (a DOR antagonist). Cell viability and morphology, as well as cell migration, were measured after drug administration. Western blotting was employed to examine the extracellular matrix (ECM) protein Fibronectin, and the tubular epithelial–mesenchymal transition (EMT) markers (E‐cadherin and α‐smooth muscle actin (α‐SMA)), signal transducer (p‐Smad3), and EMT‐regulatory gene (Snail). The expression level of phosphorylated Akt and p38 was also examined. Our results showed that TGF‐β1 induced fibroblastic appearance and increased the expression of Fibronectin, α‐SMA, P‐Smad3, and Snail, while it decreased the expression of E‐cadherin in NRK‐52E cells. Moreover, TGF‐β1 induced the activation of Akt and p38 MAPK signaling pathways. DOR activation was found to efficiently block morphological changes and cell migration, as long as the expression changes of Fibronectin, E‐cadherin, α‐SMA, P‐Smad3, Snail, P‐Akt, and P‐p38 were induced by TGF‐β1. These findings suggest that DOR may serve as an antifibrotic factor for renal proximal tubule cells by inhibiting the fibrosis process via TGF‐β/Smad, Akt, and p38 MAPK signaling pathways. Abstract : The critical role of DOR in attenuating TGF‐β1‐induced renal cell fibrosis. DOR activation differentially regulates Smad‐dependent and Smad‐independent signaling, thus controlling the EMT‐regulatory gene Snail. For protection against renal cell fibrosis induced by TGF‐β1, DOR signals function to inhibit the repressing of epithelial phenotype and gaining of mesenchymal features via directly or indirectly modulating ECM accumulation and EMT process.